2017
DOI: 10.1111/bph.13741
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin‐lowered blood glucose reduces respiratory Pseudomonas aeruginosa infection in diabetic mice

Abstract: Background and PurposeHyperglycaemia increases glucose concentrations in airway surface liquid and increases the risk of pulmonary Pseudomonas aeruginosa infection. We determined whether reduction of blood and airway glucose concentrations by the anti‐diabetic drug dapagliflozin could reduce P. aeruginosa growth/survival in the lungs of diabetic mice.Experimental ApproachThe effect of dapagliflozin on blood and airway glucose concentration, the inflammatory response and infection were investigated in C57BL/6J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 45 publications
(60 reference statements)
2
25
1
Order By: Relevance
“…4 In animal models the antihyperglycemic agents metformin and dapagliflozin reduced airway glucose concentrations and inhibited growth of S aureus or P aeruginosa . 8 , 10 , 11 However, a recent trial of metformin in hospitalized patients with COPD found no effect on inflammatory mediators or clinical outcomes. 29 In this study metformin was commenced after hospital admission, with the full dose reached after only 4 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In animal models the antihyperglycemic agents metformin and dapagliflozin reduced airway glucose concentrations and inhibited growth of S aureus or P aeruginosa . 8 , 10 , 11 However, a recent trial of metformin in hospitalized patients with COPD found no effect on inflammatory mediators or clinical outcomes. 29 In this study metformin was commenced after hospital admission, with the full dose reached after only 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus and Pseudomonas aeruginosa use glucose as a growth substrate, and their growth is promoted by high ASL glucose concentrations. 6 , 7 , 8 , 9 There is a link between increased airway glucose concentrations and bacterial colonization in animal models, 8 , 10 , 11 but the relationship between airway glucose concentrations and infection in vivo in human subjects is less well studied. One study has linked glucose in bronchial aspirates to infection with methicillin-resistant S aureus 12 ; however, sputum glucose concentrations were not related to exacerbation frequency in patients with cystic fibrosis.…”
mentioning
confidence: 99%
“…On the other hand, some studies have shown that pretreatment with dapagliflozin, a sodium-glucose co-transporter 2 inhibitor, reduced blood and bronchoalveolar lavage glucose concentrations and P. aeruginosa CFU in leptin receptor-deficient (db/db) mice, as compared to those seen in wild type (WT) mice ( 239 ).…”
Section: Methods and Inclusion Criteriamentioning
confidence: 99%
“…An additional class of anti-diabetic medications associated with lowering inflammation are the glifozins, or SGLT2 (sodium-glucose cotransporter-2/SLC5A2) inhibitors, which attenuate reabsorption of glucose in the kidney to lower blood sugar. So far, this reported anti-inflammatory effect focuses on the kidney, cardiovascular system and pancreas, rather than lungs ( 96 , 97 ), though it has been shown to indirectly reduce pulmonary infection in diabetic mice ( 98 ). Although SGLT2 inhibitors are associated with dehydration and anorexia and therefore may pose a risk for critically ill patients, a new study focusing on hospitalized adult patients with Covid-19 commenced in April 2020, with the aim of understanding the substantial cardio- and nephroprotective effects of SLGT2 inhibitors in reducing disease progression, complications, and all-cause mortality ( 99 ).…”
Section: Type 2 Diabetes Management In Covid-19mentioning
confidence: 99%